Influence of human skin injury on regeneration of sensory neurons. - Taherzadeh, O; Otto, W; Anand, U; Nanchahal, J; Anand, P (2003)
The regeneration of sensory nerve fibres is regulated by trophic factors released from their target tissue, particularly the basal epidermis, and matrix molecules. Means to modulate this response may be useful for the treatment of neuromas and painful hypertrophic scars and of sensory deficits in skin grafts and flaps. We have developed an in vitro model of sensory neuron regeneration on human skin in order to study the mechanisms of sensory dysfunction in pathological conditions. Adult rat sensory neurons were co-cultured with unfixed cryosections of normal or injured (crushed) human skin for 72 h. Neurons were immunostained for growth-associated protein-43 and the neurite lengths of neuronal cell bodies situated in various skin regions were measured. Two-way analysis of variance was performed. Neurites of sensory cell bodies on epidermis of normal skin were the shortest, with a mean +/- SEM of 75+/-10 micrometer, whereas those of cells on the dermo-epidermal junction were the longest, with a mean +/- SEM of 231+/-18 micrometer. Neurons on the dermo-epidermal junction of injured skin had significantly longer neurites than those on the same region of normal skin (mean +/- SEM = 289+/-21 micrometer). Regeneration of sensory neurons may be influenced by extracellular matrix molecules, matrix-binding growth factors and trophic factors. Altered substrate or trophic factors in injured skin may explain the increase of neurite lengths. This in vitro model may be useful for studying the molecular mechanisms of sensory recovery and the development of neuropathic pain following peripheral nerve injury.